Monetary equilibria in a cash-in-advance economy with incomplete financial markets - Jinhui H. Bai; Ingolf Schwarz (Max Planck Institute for Research on Collective Goods, 2005)
The general equilibrium model with incomplete financial markets (GEI) is extended by adding fiat money, fiscal and monetary policy and a cash-in-advance constraint. The central bank either pegs the interest rate or money supply while the fiscal authority sets a Ricardian or a non-Ricardian fiscal plan. We prove the existence of equilibria in all four scenarios. In Ricardian economies, the conditions required for existence are not more restrictive than in standard GEI. In non- Ricardian economies, the sufficient conditions for existence are more demanding. In the Ricardian economy, neither the price level nor the equivalent martingale measure are determinate.
Keywords: D52; E40; E50; 330; Money; Incomplete Markets; Fiscal Policy; Indeterminacy; Unvollkommener Markt; Cash-in-Advance-Modell; Finanzpolitik; Papierwährung; Theorie